2019
DOI: 10.1038/s41598-019-40734-z
|View full text |Cite
|
Sign up to set email alerts
|

Midbrain tectal stem cells display diverse regenerative capacities in zebrafish

Abstract: How diverse adult stem and progenitor populations regenerate tissue following damage to the brain is poorly understood. In highly regenerative vertebrates, such as zebrafish, radial-glia (RG) and neuro-epithelial-like (NE) stem/progenitor cells contribute to neuronal repair after injury. However, not all RG act as neural stem/progenitor cells during homeostasis in the zebrafish brain, questioning the role of quiescent RG (qRG) post-injury. To understand the function of qRG during regeneration, we performed a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 98 publications
1
26
0
Order By: Relevance
“…Wnt/β-catenin signaling is one of the most common intracellular signal transduction pathways activated in response to injury of virtually all tissues/organs ( Ozhan and Weidinger, 2014 ). While Wnt signaling has been revealed to promote regeneration of the optic tectum, the spinal cord, and the tectum of the midbrain in zebrafish ( Shimizu et al, 2012 , 2018 ; Strand et al, 2016 ; Wehner et al, 2017 ; Lindsey et al, 2019 ), it has not yet been associated with the regeneration of the telencephalon. We have used the Tg(6XTCF:dGFP) transgenic zebrafish reporter of Tcf/Lef-mediated transcription, which has been shown to sensitively detect Wnt/β-catenin pathway activity in several cellular contexts ( Shimizu et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Wnt/β-catenin signaling is one of the most common intracellular signal transduction pathways activated in response to injury of virtually all tissues/organs ( Ozhan and Weidinger, 2014 ). While Wnt signaling has been revealed to promote regeneration of the optic tectum, the spinal cord, and the tectum of the midbrain in zebrafish ( Shimizu et al, 2012 , 2018 ; Strand et al, 2016 ; Wehner et al, 2017 ; Lindsey et al, 2019 ), it has not yet been associated with the regeneration of the telencephalon. We have used the Tg(6XTCF:dGFP) transgenic zebrafish reporter of Tcf/Lef-mediated transcription, which has been shown to sensitively detect Wnt/β-catenin pathway activity in several cellular contexts ( Shimizu et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies come to the contradictory answers. Ohshima’s lab showed that tectal RG were capable of producing some neurons after the stab injury (~25% of newborn cells) (Shimizu et al, 2018), whereas Kaslin’s lab reported the opposite result, in which tectal RG only produce glial cells but not neurons (Lindsey et al, 2019). Using EdU pulse-and-stain assay and Cre-loxP-based clonal analysis of tectal RG, we unambiguously demonstrate at the single-cell resolution that RG give rise to newborn glial cells (~91% of total newborn cells) with only a few neurons (~3–5% of total newborn cells) after the injury (Figure 7Q), which is mostly consistent with the study of Kaslin’s lab.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other brain regions where RG present as both dormant and proliferative forms at physiological conditions, tectal RG has been reported to be dormant, and are reactivated by injury to give rise to newborn neurons via Wnt signaling as well as Notch signaling (Shimizu et al, 2018; Ueda et al, 2018). Interestingly, a recent study showed that tectal RG produced a significant number of glial cells (~25%) but not neurons (Lindsey et al, 2019). It is essential to resolve this inconsistency on the fate potentials of injury-reactivated tectal RG.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that neurogenesis in the pyramidal cell layer of the hippocampal CA1 area can promote the morphological and functional repair process after cerebral ischemia [30]. At present, it is generally believed that the enhancement of dentate gyrus neurogenesis may be a compensatory response to ischemic injury, which can promote the recovery of hippocampal function after ischemic injury [31], [32]. Studies have reported that inducing human-derived pluripotent stem cells into glial precursor cells and transplanting them into animal models of cerebral ischemia can improve the nervous system function of animals with cerebral ischemia injury [33]- [35].…”
Section: Introductionmentioning
confidence: 99%